2006
DOI: 10.1159/000091765
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Choroidal Melanoma Basal Diameter by Wide-Angle Digital Fundus Camera: A Comparison with Ultrasound Measurement

Abstract: Purpose: To compare the measurement of the basal diameter of choroidal melanoma, an important parameter for planning treatment and as a prognostic factor, by standardized ophthalmic ultrasound versus that obtained using a wide-angle fundus camera. Methods: The longest and shortest basal diameters of 104 consecutive choroidal melanomas of patients seen at the ocular oncology service of the Hadassah University Hospital were measured by B-scan ultrasound and compared with those measured by a wide-angle fundus cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…The first panoramic fundus pictures were made from a montage of 19 photographs using a movable fixation light to enable the acquisition of 96° fundus images [4]. Contact lens-based systems, including Pomerantzeff camera [5], Panoret-1000 [6], RetCam [7], and Staurenghi lens [8], provide up to 160° panoramic photographs. However, these methods require exact patient alignment, good pupillary dilation, and a skilled photographer, thus their use is impractical in clinical practice.…”
Section: Principles Of Ultra-widefield Imaging Technology Need For Dementioning
confidence: 99%
“…The first panoramic fundus pictures were made from a montage of 19 photographs using a movable fixation light to enable the acquisition of 96° fundus images [4]. Contact lens-based systems, including Pomerantzeff camera [5], Panoret-1000 [6], RetCam [7], and Staurenghi lens [8], provide up to 160° panoramic photographs. However, these methods require exact patient alignment, good pupillary dilation, and a skilled photographer, thus their use is impractical in clinical practice.…”
Section: Principles Of Ultra-widefield Imaging Technology Need For Dementioning
confidence: 99%
“…A study of 104 consecutive melanomas using the Panoret-1000 compared the measurements of the basal diameters of tumors with imaging versus ultrasound and revealed that the diameters were larger with photography than with ultrasound [52].…”
Section: Choroidal Tumors and Dystrophiesmentioning
confidence: 99%
“…14 The Panoret-1000 (Medibell Medical Vision Technologies, Ltd., Haifa, Israel) combines a contact wide-angle camera with a fiberoptic light source that is placed on the sclera. 9,15 It produces excellent pictures with high resolution and natural colours, and has successfully been deployed in ocular oncology centres. 9,15 At the time of writing this article, the Panoret-1000 is no longer commercially available.…”
Section: Wide-angle Photography and Angiographymentioning
confidence: 99%
“…9,15 It produces excellent pictures with high resolution and natural colours, and has successfully been deployed in ocular oncology centres. 9,15 At the time of writing this article, the Panoret-1000 is no longer commercially available.…”
Section: Wide-angle Photography and Angiographymentioning
confidence: 99%